Complete chloroplast genome of Meconopsis integrifolia (Papaveraceae) - Rui Li; Xianye Ma; Xiaofeng Zhang; Dangwei Zhou; Huan Wang; Tingfeng Cheng; Wenjuan Wang (Mitochondrial DNA. Part B. Resources, 2020)
Meconopsis integrifolia (Maxim.) Franch is a traditional Tibetan medicinal material. In this study, we sequenced and assembled the complete chloroplast genome of M. integrifolia. The chloroplast genome is 152,714 bp in length, containing a pair of inverted repeated (IR) region of 25,627 bp that are separated by a large single copy (LSC) region of 83,706 bp, and a small single copy (SSC) region of 17,754 bp. Moreover, a total of 126 functional genes were annotated, including 86 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. In the maximum likelihood phylogenetic tree, M. integrifolia clustered closely with three Papaver species.